Analisis Risiko Produksi dan Nilai Tambah Kedelai Sebagai Bahan Baku Pembuatan Tempe di Kecamatan Buay Madang Kabupaten Oku Timur - Sagita, Yoka; Ogari, Putri Ayu; Pusvita, Ema (Universitas Galuh, 2025)
In the tempe making business, problems often occur that pose a high risk of loss. Production risk is the potential for undesirable events or conditions to occur that can disrupt or hinder the production process, resulting in a reduction in quality, quantity, or even stopping production. Business or activity of processing raw materials and semi-finished goods to add value and make a profit. This research aims to analyze the level of production risk experienced when processing soybeans as raw material for making tempeh in Buay Madang District, East OKU Regency. And to find out the amount of added value obtained from processing soybeans as raw material for making tempeh in Buay Madang District, East OKU Regency. The results of this research show that the business of processing soybeans into tempeh has an average total revenue received by tempeh producers of IDR 2,661,933. The tempeh business in Buay Madang District, OKU Timur, was declared to be protected from losses. This can be seen from the coefficient of variation (CV) value of less than 0.5, namely 0.02 and the lower limit (L) of more than 0, namely 2,581,731. and the business of processing soybeans into tempeh provides added value of IDR 1,368.32.